Practices and Transformations in Luxury Hospitality (An Analysis of Successful Sustainable Practices and Innovation Integration Models) - Emilova, Irena (Research Papers, 2025)
This paper examines the role of sustainable innovations in luxury hospitality as a strategic tool for enhancing competitiveness, social relevance, and ecological responsibility. The study includes international and Bulgarian case studies (comparative analysis). The aim is to develop an integrative model that combines technological, social, architectural, and business innovations. The methodology involves a systematic literature review and analysis of international and Bulgarian case studies (Six Senses, 1 Hotels, Svart Hotel, Maslina Resort, Albena Resort, InterContinental Sofia, Kempinski Grand Arena Bansko, Zornitza Family Estate). The findings reveal that luxury hospitality functions as a laboratory for sustainable transformation, shifting the meaning of luxury from prestige and status toward responsibility and conscious experiences. A key limitation is the conceptual nature of the study and the lack of primary data, but its contribution lies in proposing a model with practical value for management and strategic planning.
Keywords: Luxury hospitality; Sustainable tourism; Sustainable innovation; Competitive advantage; ESG; Mindful luxury; Experience design